1988
DOI: 10.1097/00000658-198802000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Dumping Syndrome with the Somatostatin Analogue SMS 201–995

Abstract: In six patients suffering from severe early dumping and six patients with late dumping after peptic ulcer surgery, the effect of the somatostatin analogue SMS 201-995 was compared with placebo. In early dumpers subcutaneous administration of 50 micrograms SMS 201-995 prior to meal ingestion induced a strong improvement of dumping symptoms as reflected by a decrease of the Sigstad dumping score from 12 +/- 2 during placebo to 5 +/- 2 (p less than 0.05). Furthermore, the postprandial increase of pulse rate was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…Somatostatin analogs such as octreotide have been used successfully in the treatment of early dumping syndrome [12][13][14][15], although octreotide does have problems, including being expensive and having adverse events, such as gallstone formation, prolonged QT and such as postprandial hyperglycemia. The data shown here suggest that increased secretion of GLP-1 and GIP might be an alternative mechanism leading to the occurrence of early dumping syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin analogs such as octreotide have been used successfully in the treatment of early dumping syndrome [12][13][14][15], although octreotide does have problems, including being expensive and having adverse events, such as gallstone formation, prolonged QT and such as postprandial hyperglycemia. The data shown here suggest that increased secretion of GLP-1 and GIP might be an alternative mechanism leading to the occurrence of early dumping syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…These encouraging reports with somatostatin were soon followed by several studies with the analogue, octreotide (table 1). Although the total number of patients studied remains relatively small, the results show unani mously that octreotide 50-100 pg can almost completely relieve the symptoms of dumping induced by a standard glucose load or a meal [2,[5][6][7], Objective evidence of dumping, namely rise in pulse rate, occurred in all studies and this was also inhibited by octreotide. In three of the studies octreotide also prevented the rise in PCV [2,6,7], Two studies have examined the effect of octreotide long-term in dumping syndrome (table 2).…”
Section: Clinical Studiesmentioning
confidence: 77%
“…Evi dence, that inhibition of motility is contributory is pro vided by the study of Geer et al [2] which showed that octreotide substantially delays gastric emptying in pa tients with dumping syndrome (578 ± 244 min) com pared to controls treated with placebo (76 ± 23 min). Pre liminary evidence suggests that octreotide increases small bowel transit time in some patients with dumping syn drome [5].…”
Section: Mechanism O F Actionmentioning
confidence: 99%
“…Similar increases have been reported previously in gastrectomized patients with symptoms of dumping [4,5], High doses of neurotensin cause vasodilatation; however, current evidence suggests that it is unlikely that this peptide plays a role in the pathophysiology of dumping [37], On the contrary, since both neurotensin and PYY have inhibitory effects on upper gastrointestinal motility and secretion, these in creased responses appear to be adaptive changes which tend to slow transit and improve absorption [ Long et al [43] reported that somatostatin infusion reduced the symptoms of the dumping syndrome with a corresponding decrease in secretion of peptides such as neurotensin and vasoactive intestinal polypeptide. More recent reports suggest that long-acting somatostatin ana logues offer promise in treating the condition [44,45], It is interesting that somatostatin not only slows bowel transit but also stimulates esophageal motor activity [46]. Total gastrectomy patients have more severe symptoms of re flux esophagitis and a lower nutritional state than those after distal partial gastrectomy.…”
Section: Discussionmentioning
confidence: 99%